On condensed set in ideal topological spaces. Issue 5 (4th July 2022) - Abdalbaqi, Luma S.; Hadi, Mustafa Hasan; Al-Swidi, Luay A.
Abstract: The research relied on two basic and new concepts, starting from the first concept of condensed, which is divided into four different types, where the relationships between them were studied, as well as their relationship to the concept of I-dense, I-irresolvable and other basic concepts in the ideal topological spaces. The second concept is the I-extremal disconnected, and we have shown relationship with the first concept.